Pelatihan Kepemimpinan Bagi Karyawan Generasi Z di Perusahaan Kargo Internasional: Strategi dan Implementasi - Primadi Candra Susanto; Olfebri Olfebri; Aswanti Setyawati; Rohana Sitanggang; Reza Fauzi Jaya Sakti (Jurnal Kemitraan Masyarakat, 2025)
This Community Service Program was conducted to enhance the competencies of supervisors in the logistics and transportation division of an international cargo company through leadership training tailored to the characteristics of Generation Z. The program aimed to strengthen participants’ capabilities in managing workplace dynamics, improving team communication, and promoting more effective performance through a flexible leadership approach. The training was held on November 18, 2025, at the company’s head office in Bekasi and was attended by 16 supervisors. The methods used included material presentations, group discussions, case study analysis, and an interactive question-and-answer session. The results indicate an increased understanding among participants regarding Generation Z work behavior, appropriate leadership principles, and more adaptive management strategies. This program is expected to provide sustainable benefits for human resource development and to enhance leadership effectiveness within the logistics sector.